2018
DOI: 10.1088/1361-6579/aab1a4
|View full text |Cite
|
Sign up to set email alerts
|

Novel optical assessments of tissue composition and viability using fluorescence spectroscopy and tissue oxygenation spectrophotometry in patients with systemic sclerosis: a pilot study

Abstract: The results of this pilot study demonstrate the potential diagnostic utility of FS and TOS assessments in SSc patients and further work is now needed to validate these techniques prospectively in a larger group of SSc patients across the spectrum of the disease, and also patients with other types of vasculopathy and conditions that can cause skin fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Increased oxidative stress, observed as an increase in skin autofluorescence, has been observed in patients with SSc in previous studies ( Allen et al, 2018 ; Murray et al, 2012 ; Dadoniene et al, 2015 ). In previous work we found increased oxidative stress (versus controls) at the proximal finger, hand and forearm but not at the distal finger ( Murray et al, 2012 ).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Increased oxidative stress, observed as an increase in skin autofluorescence, has been observed in patients with SSc in previous studies ( Allen et al, 2018 ; Murray et al, 2012 ; Dadoniene et al, 2015 ). In previous work we found increased oxidative stress (versus controls) at the proximal finger, hand and forearm but not at the distal finger ( Murray et al, 2012 ).…”
Section: Discussionsupporting
confidence: 68%
“…In previous work we found increased oxidative stress (versus controls) at the proximal finger, hand and forearm but not at the distal finger ( Murray et al, 2012 ). Allen et al identified increased skin fluorescence and decreased oxygenation in 14 patients with SSc, compared to 9 controls ( Allen et al, 2018 ). Dadoniene et al measured oxidative stress at the forearm that was associated with changes in finger perfusion under occlusion in 47 patients with SSc versus 47 healthy controls ( Dadoniene et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the fibrotic process, the functional relevance of the elevated oxidative stress components in the circulation of SSc patients was evidenced in one study showing that sera from patients with SSc pulmonary hypertension caused oxidative stress-induced stimulation of collagen synthesis in human pulmonary smooth muscle cells in vitro [ 51 ], and the demonstration by Sambo et al [ 8 ], in which the increased levels of ROS in SSc dermal fibroblasts resulted in the establishment of a pro-fibrotic phenotype in these cells. More recently, extensive investigations have assessed cutaneous oxidative stress in SSc, employing novel quantitative methods including fluorescence spectroscopy and tissue oxygenation spectrophotometry of affected SSc skin [ 52 , 53 ]. These studies suggested that the structural and functional microvascular abnormalities characteristic of the SSc vasculopathy cause tissue hypoxia and that as a result, there is increased oxidative stress in the affected tissues [ 52 , 53 ].…”
Section: Role Of Ros In Ssc Pathogenesismentioning
confidence: 99%
“…More recently, extensive investigations have assessed cutaneous oxidative stress in SSc, employing novel quantitative methods including fluorescence spectroscopy and tissue oxygenation spectrophotometry of affected SSc skin [ 52 , 53 ]. These studies suggested that the structural and functional microvascular abnormalities characteristic of the SSc vasculopathy cause tissue hypoxia and that as a result, there is increased oxidative stress in the affected tissues [ 52 , 53 ]. Furthermore, several studies have indicated that the increased oxidative stress induced by ROS alterations is reflected in the extent and severity of cutaneous fibrotic and skin thickening in these patients [ 24 , 27 , 54 , 55 ].…”
Section: Role Of Ros In Ssc Pathogenesismentioning
confidence: 99%